Distinct Immune Phenotypes and Cytokine Profiles in Children with Differing Severity of COVID-19. Issue 11 (24th August 2022) - Talarico, Laura Beatriz; Toledano, Analía; Contrini, María Marta; Torrado, Lidia E.; Martínez, María Paula; Gaillard, María Isabel; Caratozzolo, Ana; Byrne, Alana Brooke; Bonnin, Florencia Agustina; Tineo, María Soledad; Yfran, Eduardo Walter; Acosta, Patricio Leandro; et al.
Abstract : Background: Coronavirus disease 2019 (COVID-19) is usually mild and self-limited in children. However, a few Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infections in children may progress to severe disease with respiratory distress or can result in a multisystem inflammatory syndrome (MIS-C) associated with COVID-19. The immune mechanisms for these differential clinical outcomes are largely unknown. Methods: A prospective cohort study was performed to analyze the laboratory parameters, antibody response, immune phenotypes and cytokine profiles of 51 children with different clinical presentations of COVID-19. Results: We found that the absolute lymphocyte counts gradually decreased with disease severity. Furthermore, SARS-CoV-2 IgG levels in the acute phase and convalescence were not significantly different in patients with different disease severity. A decrease in CD3 +, CD4 + and CD8 + T cells was observed as disease severity increased. Both CD4 + and CD8 + T cells were activated in children with COVID-19, but no difference in the percentage of HLADR + -expressing cells was detected across the severity groups. In contrast, MIS-C patients exhibited augmented exhausted effector memory CD8 + T cells. Interestingly, the cytokine profile in sera of moderate/severe and MIS-C patients revealed an increase in anti-inflammatory IL-1RA and a suppression of tumor necrosis factor-α, RANTES, eotaxin and PDGF-BB. MIS-C patients also exhibited augmented IL-1β. Conclusions: We report distinct immune profiles dependent on severity in pediatric COVID-19 patients. Further investigation in a larger population will help unravel the immune mechanisms underlying pediatric COVID-19.